2019
DOI: 10.1021/jacs.9b03680
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Oxidation of a Tyrosine by Proton-Coupled Electron Transfer Promotes Light Activation of an Animal-like Cryptochrome

Abstract: The animal-like cryptochrome of Chlamydomonas reinhardtii (CraCRY) is a recently discovered photoreceptor that controls the transcriptional profile and sexual life cycle of this alga by both blue and red light. CraCRY has the uncommon feature of efficient formation and longevity of the semi-reduced neutral form of its FAD cofactor upon blue light illumination. Tyrosine Y 373 plays hereby a crucial role by elongating as fourth member the electron transfer (ET) chain that comprises the tryptophan triad otherwise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 107 publications
(350 reference statements)
7
81
0
1
Order By: Relevance
“…[57][58][59][60] Herein, hydrogen donation is not limited to the typical hydrogen-atom-transfer; other antioxidant pathways could also result in hydrogen donation, such as proton-coupled electron transfer. 54,55,[61][62][63] The hydrogen donation and subsequent dimerization reactions are shown in Fig. 4, where the isorhapontigenin was linked at 2,5 0 in agreement with the results of previous studies [57][58][59][60][61][62][63][64][65][66][67] and our MS analysis (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…[57][58][59][60] Herein, hydrogen donation is not limited to the typical hydrogen-atom-transfer; other antioxidant pathways could also result in hydrogen donation, such as proton-coupled electron transfer. 54,55,[61][62][63] The hydrogen donation and subsequent dimerization reactions are shown in Fig. 4, where the isorhapontigenin was linked at 2,5 0 in agreement with the results of previous studies [57][58][59][60][61][62][63][64][65][66][67] and our MS analysis (Fig.…”
Section: Resultssupporting
confidence: 91%
“…14,15,[51][52][53] However, electron donation is always accompanied by proton donation in cells. 54,55 The net result of electron and proton donation is generally equivalent to that of whole hydrogen donation.…”
Section: Resultsmentioning
confidence: 99%
“…21 Similar reaction products have later also been observed upon excitation of oxidized flavin in the related cryptochrome blue-light sensors. 16,22,23 More recently, the flavin excited state quenching by tryptophan has been examined in detail in artificial protein maquettes. 24,25 In contrast to tryptophan, for a long time it had been assumed that the oxidation of tyrosine is necessarily accompanied by a concerted deprotonation due to its extremely low pKa (~−2).…”
Section: Introductionmentioning
confidence: 99%
“…Chlamydomonas reinhardtii (400-480 fs) 47,81 and two flavoproteins of the cryptochrome photolyase family from the green algae Ostreococcus tauri (390-590 fs). 124 Note that the absorption spectra of adenine and the adenine radical cation have not been included in the experimental analysis, and the fs-ps time-resolved spectroscopy experiments have been conducted on the different proteins, not on the one from Arabidopsis thaliana used in our simulations.…”
Section: Theoretical Rate Constants and Quantum Yields In Relation Tomentioning
confidence: 99%
“…45 The tyrosyl radical, for which the hyperfine couplings are as strong as for the tryptophan radical, 27,46 is experimentally found to be formed on the microsecond timescale in the plant cryptochrome. 41 Moreover, it has been recently reported that the tyrosine Y373 serves as the fourth electron donor in the ET/proton-coupled ET chain in the cryptochrome from Chlamydomonas reinhardtii with a radical pair lifetime of ≈ 50 ms. 47 Therefore, despite thorough and extensive theoretical and experimental studies of cryptochromes and their homologs, mechanistic features of the PET specifically for cryptochromes are still missing. The present work revisits and sheds new light on the role of FAD itself, and cellular metabolites, in photoactivation of cryptochromes.…”
Section: Introductionmentioning
confidence: 99%